(untitled) (Journal of Laboratory Animal Science, 2024)
Bedding and nesting material provided in cages for laboratory rats has important consequences on welfare, directly through the comfort and utility in behaviour such as nest building, and indirectly through properties such as air quality. A study was conducted at Small Animal House, Veterinary College, Bangalore to find out effect of different bedding materials on the reproductive performance of laboratory rats. Thirty Wistar female rats were divided into three groups and subjected to the different bedding material used – paddy husk (PH), corncob (CC) and wood shavings (WS). Litter size and litter weight were recorded at birth and at weaning (day 21). Bedding material significantly (P<0.05) influenced litter size at birth, where it was significantly higher in WS (8.06±0.31) and PH (8.03±0.31) than in CC (6.8±0.3). Litter weight was higher in WS at all times, though not significantly (P>0.05) different from the other groups. The results indicate that wood shavings and corncob may be suitably used as alternative to other bedding materials for laboratory rats.